Procedure for Birth Registration Services for Children whose parents are not known at the Population Service and Civil Registration of Soppeng Regency - Sirajuddin Saleh; Andi Adhe Amalya; Muh. Nasrullah (Jurnal Ad'ministrare, 2022)
The Population and Civil Registration Office is a Regional Apparatus Organization established based on the Soppeng Regency Regional Regulation Number 5 of 2016. The purpose of this study was to determine the application of service procedures and factors supporting and inhibiting birth registration for children whose parents did not know about the Department of Population and Civil Registration of Soppeng Regency. The results showed that the application of birth registration service procedures for children whose parents did not know started from service procedures, completion time, service fees, service products, facilities and infrastructure, and competence of service providers has been carried out in accordance with Standard Operating Procedures and is categorized as good. This research can be used as a reference in the application of standard operating procedures for making birth certificates for children whose parents do not know at the Population and Civil Registration Office because previous studies have focused on legal guarantees and children's rights whose parents do not know about birth certificates